Effectiveness of a novel traction device (TRACMOTION) for endoscopic submucosal dissection using a scissor‐type knife: An animal pilot study and clinical experiences - Yuko Miura; Yosuke Tsuji; Ryohei Miyata; Ayano Fujisawa; Hiroyuki Tsukihara; Mitsuhiro Fujishiro (DEN Open)
Abstract A newly developed articulated through‐the‐scope traction device, TRACMOTION, has been used clinically for endoscopic submucosal dissection (ESD). However, there are few reports on the characteristics of this device and the lesion types for which it is most effective. Therefore, we evaluated its optimal use, efficacy, and safety clinically in animals. Subsequently, we confirmed the safety and efficacy of ESD using this device in humans. Two live swine were used; one underwent conventional ESD (C‐ESD) and the other traction‐assisted ESD (T‐ESD). To examine the traction effect at each resection site, three ESD ulcers (greater curvature/anterior wall/posterior wall) with a diameter of approximately 40 mm were created in each swine. Based on our preliminary experiments, scissor‐type and needle‐type knives were used in the T‐ESD and C‐ESD groups, respectively. The primary endpoint was the resection speed, and the secondary endpoint was the degree of muscle layer damage. T‐ESD was faster than C‐ESD on the posterior wall, similar to the greater curvature, and T‐ESD was slower than C‐ESD on the anterior wall. There were no cases of intraoperative perforations. Obvious muscle layer damage was observed in post‐C‐ESD wounds on the anterior wall. The submucosal layer was retained in all post‐T‐ESD wounds. Although this study showed that ESD with TRACMOTION may be safe and effective, it is necessary to consider that it may be unsuitable for some lesions. This may be due to device characteristics and requires further validation.